2022
DOI: 10.3390/app12157548
|View full text |Cite
|
Sign up to set email alerts
|

Early Earthquake Detection Using Batch Normalization Graph Convolutional Neural Network (BNGCNN)

Abstract: Earthquake is a major hazard to humans, buildings, and infrastructure. Early warning systems should detect an earthquake and issue a warning with earthquake information such as location, magnitude, and depth. Earthquake detection from raw waveform data using deep learning models such as graph neural networks (GNN) is becoming an important research area. The multilayered structure of the GNN with a number of epochs takes more training time. It is also hard to train the model with saturating nonlinearities. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Figure 1c represents a layered architecture similar to the model architecture proposed by Ref. [20], where the fourth layer is the batch normalization layer. Overfitting is prevented through batch normalization and dropout regularization, which ensure that the input distribution does not differ between layers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1c represents a layered architecture similar to the model architecture proposed by Ref. [20], where the fourth layer is the batch normalization layer. Overfitting is prevented through batch normalization and dropout regularization, which ensure that the input distribution does not differ between layers.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1e shows the proposed CNN block that consists of five layers: convolutional, batch normalization, activation, pooling, and attention layers. The proposed architecture is the combination of Figure 1c [16] and Figure 1d [20]. Experiments on two seismic datasets show that our proposed model outperforms the baseline models of GCNN given in Figure 1a-c as it uses both batch normalization and attention layers to achieve high accuracy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that GNNs have the potential to deal with irregularly spaced stations for phase association and event localization [14,16,[35][36][37][38][39]. Here, we build a graph-based network (Fig.…”
Section: Graph Based Neural Networkmentioning
confidence: 99%
“…A standard earthquake monitoring workflow involves a series of steps to detect and characterize earthquakes, including phase picking, association, and event location [1][2][3]. Phase picking, a conceptually simple task which is akin to detection problems in computer vision, has recently been improved through deep learning [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], where convolutional neural networks (CNNs) [19] are typically used. After the phase picking, traditional [20][21][22][23] and deeplearning-based [24][25][26] phase association algorithms have been used to link seismic phases at multiple stations from the same events.…”
Section: Introductionmentioning
confidence: 99%